Factor VIIa in Patients with C1-Inhibitor Deficiency - Nielsen, Erik Waage; Morrissey, James; Olsen, Jan Ole; Østerud, Bjarne (Thrombosis and Haemostasis, 1995)
In hereditary angioedema (HAE), normal C1-inhibitor (CI-INH) is low and the contact system aetivated. Recently, the findings of a tissue factor mutant selectively deficient in promoting the conversion of FVII to FVIIa, but with retained cofactor for FVIIa, made it possible to examine reliably the pre-existing content of FVIIa in HAH patients. This was of interest as FXIIa (mainly inhibited by (CI-INH) is able to activate FVII directly. FVIIa in 21 remission HAH patients were within normal limits but nearly doubled as compared to their 23 normal siblings (p = 0.0017). Cold promoted activation of FVII (CPA) (common Clot assay) was displayed in plasma of all 5 untreated patients (CI-INH function <35%), but not in plasma of 2 patients treated prophylactically with danazol (CI-INH function about 40%). These results suggest that there is a minute, yet significant activation of FVII in patients with CI-INH deficiency.